Valuing the endangered species Antirrhinum lopesianum: neuroprotective activities and strategies for in vitro plant propagation - Gomes, Andreia (2014)
Plant phytochemicals are described as possessing considerable neuroprotective properties, due to radical scavenging capacity and acetylcholinesterase inhibitory activity, important bioactivities in neurodegeneration. Antirrhinum lopesianum is a rare endemism from the Iberian Peninsula, occurring at the northeastern border between Portugal and Spain. It is classified as Endangered, due to its highly fragmented geographical occupation, facing a high risk of extinction in the Portuguese territory, within 20 years. Here, we describe for the first time the chemical characterization of extracts of the species concerning total phenol content, flavonoid content and antioxidant properties. The profile of high performance liquid chromatography with diode array detector (HPLC-DAD) of the polyphenol-enriched fraction of plant extracts was also performed, showing the great potential of the species as a source of bioactive phytochemical compounds. A. lopesianum’s potential for neuroprotection was revealed by a significant acetylcholinesterase inhibitory activity and also by a neuroprotective effect on a human cell model of neurodegeneration. Moreover, this is the first report describing a successful procedure for the in vitro propagation of this endangered species. The comparison of phenolic content and the HPLC-DAD profile of wild and in vitro propagated plants revealed that in vitro plants maintain the ability to produce secondary metabolites, but the profiles are differentially affected by the growth regulators. The results presented here greatly contribute to the value for this species regarding its potential as a source of phytochemicals with prospective neuroprotective health benefits.